Micro Irrigation and NPK Fertilization to Improve Nutrient Uptake and Flavonoid of Shallot in Karst Land - Nana, Fransiska Maria Aprilya; Murtiningrum; Zaki , Muhamad Khoiru; Ximenis, Virgolie Diknas; Ngadisih; Maftukhah, Rizki; Fahima, Sahidatun (Research and Social Study Institute, 2025)
Background: Water and nutrient limitations in karst soils hinder the optimal growth of shallots, so water and nutrient management is carried out using variations in micro-irrigation and NPK fertilization. Variations in micro-irrigation and NPK fertilization can support the growth and flavonoid content of shallots.Aims: This study aims to analyze nutrient uptake and total flavonoid production of shallots in karst soils with variations in micro-irrigation and NPK fertilization.Methods: The research used a Randomized Block Design (RBD) containing two main factors. The first factor was the irrigation technique, consisting drip irrigation (I1) and mist irrigation (I2). The second factor was the NPK fertilizer dosage, consisting three levels: 0 kg/ha (N1), 500 kg/ha (N2), and 1000 kg/ha (N3). The parameters observed included soil moisture, soil NPK availability, plant NPK uptake, total flavonoids, growth, and shallot yield.Results: The results showed that mist irrigation with an NPK dose of 1000 kg/ha yielded higher results compared to drip irrigation in terms of soil moisture, NPK availability and uptake, growth, and yield. The highest availability of nitrogen, phosphorus, and potassium in mist irrigation with a dose of 1000 kg/ha was 0.36%, 89.20 ppm, and 0.66 me%, respectively. Phosphorus uptake in mist irrigation was higher than in drip irrigation, at 0.81% and 0.89%, respectively. Growth and yield under mist irrigation with an NPK dose of 1000 kg/ha also yielded the best results compared to drip irrigation with an NPK dose of 1000 kg/ha, namely plant height (30.69 and 29.74 cm), number of leaves (27.65 and 25.77 leaves), and bulb diameter (30.07 and 27.02 mm). The highest total flavonoid content was observed in drip irrigation with a 500 kg/ha dose compared to mist irrigation with a 500 kg/ha dose, namely (78.83 and 50.96 mg/kg). Overall, irrigation techniques with varying NPK doses were able to increase nutrient and flavonoid uptake in shallot on karst land.